2016
DOI: 10.1080/09540121.2016.1146212
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and willingness to use HIV pre-exposure prophylaxis among HIV-negative men who have sex with men in Switzerland

Abstract: Pre-exposure prophylaxis (PrEP) is discussed as an additional HIV prevention method targeting men who have sex with men (MSM). So far, PrEP has not been approved in Switzerland and only little is known about the acceptability of PrEP among MSM living in Switzerland. Given the slow uptake of PrEP among MSM in the USA, the objectives of the study were to investigate the acceptability for PrEP and to identify factors influencing the acceptability for this prevention method and the willingness to adopt it. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…The main reasons for Kazakhstani MSM to be interested in PrEP related to increased safety and control of HIV prevention. Interviewees revealed severe anxiety about HIV transmission and were enthusiastic about additional protection, similar to findings from previous qualitative studies in which PrEP was regarded as an option to engage in worry free sex, and as protection that is independent of sexual partners' behaviour [36,37]. This anticipated empowering effect was confirmed by Collins et al [38] who showed that PrEP "reduced fear and shame associated with sex and facilitated greater sexual satisfaction and intimacy" (p. 55).…”
Section: Discussionsupporting
confidence: 74%
“…The main reasons for Kazakhstani MSM to be interested in PrEP related to increased safety and control of HIV prevention. Interviewees revealed severe anxiety about HIV transmission and were enthusiastic about additional protection, similar to findings from previous qualitative studies in which PrEP was regarded as an option to engage in worry free sex, and as protection that is independent of sexual partners' behaviour [36,37]. This anticipated empowering effect was confirmed by Collins et al [38] who showed that PrEP "reduced fear and shame associated with sex and facilitated greater sexual satisfaction and intimacy" (p. 55).…”
Section: Discussionsupporting
confidence: 74%
“…As observed in the 2012 study, this includes increasing PrEP knowledge; addressing psychosocial determinants such as feelings of shame and perception of self-efficacy; and encouraging the use of condoms or other risk reduction strategies alongside increasing PrEP accessibility [ 11 , 21 ]. We furthermore expect PrEP intention and use to increase with increasing awareness and decreasing PrEP costs [ 10 , 20 22 ]. This is supported by the observed increasing proportion of recent self-obtaining PrEP users.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis estimated the acceptability of using PrEP among MSM to be 57.8% globally [ 7 ]. Outside of Asia, research on acceptability of PrEP among MSM has been conducted mostly in the United States of America [ 8 22 ], followed by United Kingdom [ 23 26 ], Australia [ 27 29 ], Brazil [ 30 ], Canada [ 31 33 ], France [ 34 , 35 ], Kenya [ 36 ], Netherlands[ 37 ], Peru [ 38 ], Portugal [ 39 ], Switzerland[ 40 ], and Spain [ 41 ]. Other studies have assessed acceptability of PrEP using surveys that included MSM from multiple countries [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%